Managing workplace bullying. How to identify, respond to and manage bullying behavior in the workplace - Oade, Aryanne (Basingstoke, 2010)
"This is a comprehensive, practical and engaging book designed to help readers to recognise bullying behaviour at work and identify and select inter-personal strategies for handling bullying behaviour."